Niobium and chromium rich coatings tailored by laser alloying: XRD analysis at high temperatures - Costa,Adilson Rodrigues da (2004)
Laser treatment technologies have been widely used to modify superficial layers of different materials. In this work we prepare Nb and Cr rich coatings according to laser alloying technique using cast iron as substrate material. Nb and Cr are intensive used in order to overcome challenges like good chemical and mechanical performance at high temperatures. Following laser alloying the surface-modified samples were submitted to an "in situ" XRD analysis under controlled high temperature and atmosphere. The phase transitions registered point to transformations that do not implies formation of fragile phases or cracks induced by high volumes modifications.